Corporate Da’wa Based on Spiritual Capital: Internalizing the Concept of Ihsan in Corporate Work Culture in Indonesia - Abdul Mujib; Ridwan Rustandi; Asep Iwan Setiawan (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2025)
This research analyzed the internalization of the Islamic concept of ihsan as a form of social capital integrated into corporate work culture to strengthen leadership competencies and human resource development. The focus is on implementing spirituality in work culture and identifying institutional da'wa values embedded in management practices. Using a constructivist paradigm and a qualitative case study method, this research explored ihsan within the work culture practiced by the Human Capital Division's Sub-Division of Spiritual Capital Management at PT Telkom. Data was collected through observations, interviews, and document analysis concerning corporate da'wa activities aligned with the spiritual capital approach. The findings revealed a spiritually driven work culture reflected in "The Telkom Way" operationalized through three foundational elements: philosophy, principles, and practices (3P). The work culture serves as spiritual capital, measurably impacting organizational performance through enhanced service quality metrics and employee satisfaction through improved workplace spiritual well-being assessments. The concept of ihsan is strongly related to the "Always the Best" work ethic promoted within the company, emphasizing excellence in service as a form of devotion, benefiting individuals, teams, and society. From a corporate da'wa perspective, "The Telkom Way" represents integrating Islamic values into the modern business context. The core philosophy of ihsan, embodied in the "Always the Best" principle, manifests Islamic teachings on excellence and integrity in professional conduct. This research contributes to the development of institutional da'wa perspectives as a foundational value influencing the corporate culture of major Indonesian organizations, while also analyzing the synergy between spirituality and business practices in a Muslim-majority context through quantifiable evidence of improved organizational outcomes and employee well-being indicators.